Southeast Asia - Dobby, Ernest Henry George (University of London Press, 1967)
This book is divided into three parts. The first pictures the natural setting, the second gives a regional treatment of the human details of each political unit, and the third ties together the social geography of Southeast Asia, to pose some of its present problems.